The Palm Beach County School Safety and Student Performance Partnership Research Project, Palm Beach, Florida, 2014-2018 - Mears, Daniel P. ([Verlag nicht ermittelbar], 2019)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study evaluated a school-based, wraparound intervention for police- and court-involved youth in four high schools in Florida's School District of Palm Beach County. The intervention involved a collaboration between the schools, school police, the juvenile court, and several service providers. The collection contains 1 Stata data file (Data.dta (n=863; 118 variables)) and 1 Stata program file (Syntax.do).